I would like to prove that $\sum_{n=1}^\infty \frac{x^2}{(1+x^2)^n}$ converges for $x\in[-1,1]$, but not uniformly. Pointwise convergence is easy.

Define $S_n(x)=\sum_{k=1}^n \frac{x^2}{(1+x^2)^k}$.

$\frac{x^2}{(1+x^2)^n}\leq \left(\frac{x^2}{1+x^2}\right)^n\forall x\in[-1,1]$.

$\forall x\in[-1,1]\cap\{0\}$, $\sum_{n=1}^\infty\left(\frac{x^2}{1+x^2}\right)^n$ is a geometric series and converges to $\frac{1}{1-\frac{x^2}{1+x^2}}$. By the comparison test, $S_n(x)$ converges $\forall x\in[-1,1]\cap\{0\}.$ $S_n(0)=0 \forall n\in\mathbb{N}^*$.

Uniform convergence is proving much trickier. I've been trying to show that for some $x$ that is dependent on $n$, $S_n(x)$ is constant, which seems to be a commonly used trick to show something doesn't uniformly converge. I plotted part of the sum, and it looks like around $x=.05$, for sufficiently large $n$, $S_n(x)$ jumps from 0 to 1. Though I have no idea where I can pull this number out of the series.

  • $\begingroup$ Your series is Geometric, with ratio $1/(1+x^2)$. Compute its sum. You'll note the pointwise limit function is not continuous at $0$. $\endgroup$ Dec 14 '15 at 15:08
  • $\begingroup$ By the way, your initial inequality does not hold. $\endgroup$ Dec 14 '15 at 15:10


Assume $x\in\mathbb{R}$:

$$\sum_{n=1}^{\infty}\frac{x^2}{\left(1+x^2\right)^n}=\lim_{m\to\infty}\sum_{n=1}^{m}\frac{x^2}{\left(1+x^2\right)^n}=\lim_{m\to\infty}\left(1-\frac{1}{\left(x^2+1\right)^m}\right)=$$ $$1-\lim_{m\to\infty}\frac{1}{\left(x^2+1\right)^m}=1-\frac{1}{\lim_{m\to\infty}\left(x^2+1\right)^m}=1-0=1$$

So we can say that:

$$\sum_{n=1}^{\infty}\frac{x^2}{\left(1+x^2\right)^n}\space\space\text{converges when}\space\frac{1}{|x^2+1|}<1$$


Define a sequence of functions $f_N: [-1,1] \rightarrow \mathbb{R}$, $N = 1, 2, 3, ...$ by $$f_N(x) = \sum\limits_{n=1}^{N} \frac{x^2}{(1+x^2)^n}$$ Then $f_N(x)$ converges pointwise to the function $f(x) = \sum\limits_{n=1}^{\infty} \frac{x^2}{(1+x^2)^n}$. If $f_N$ converged uniformly to $f(x)$, then $f(x)$ would be a continuous function $[-1,1] \rightarrow \mathbb{R}$, since each function $f_N$ is continuous.

However, for $0 \neq x \in [-1,1]$, we have $$f(x) = x^2 \sum\limits_{n=1}^{\infty} \frac{1}{(1+x^2)^n} = \frac{x^2}{(1+x^2)} \frac{1}{(1- \frac{1}{1+x^2})} = \frac{x^2}{x^2} = 1$$ Here since $|\frac{1}{1+x^2}| < 1$ for $x \neq 0$, I can legally take $x^2$ out of the infinite sum, because the geometric series $\sum\limits_{n=1}^{\infty} \frac{1}{(1+x^2)^n}$ will converge on its own. On the other hand, $f(0) = 0$. So $f$ is not continuous.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.